Nilai Dakwah dalam Novel Perjalanan Cinta ke Hagia Sophia Karya Melisa Ode Kamil - Melisa Ode Kamil; Ade Fadli Fachrul (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2025)
Novels as popular literary works do not merely function as entertainment; they also serve as meaningful media for conveying moral messages and da’wah values. The novel Perjalanan Cinta ke Hagia Sophia (Journey of Love to Hagia Sophia) presents a compelling blend of romance, historical background, and Islamic spirituality, making it significant to examine from the perspective of da’wah studies. This research aims to identify and analyze the da’wah values embedded in the novel, particularly those related to aqidah, akhlaq, and ibadah. The study employs a qualitative content analysis method by closely examining the text, selecting relevant quotations containing da’wah messages, and classifying them according to established categories of da’wah values. The findings reveal that the novel effectively functions as a contemporary medium of da’wah, integrating Islamic teachings within a romantic narrative framework that appeals to younger readers. The interconnected values of tawhid, moral conduct, and worship practices are harmoniously woven into an educational and inspirational storyline. Future research is recommended to explore its influence on modern Muslim readers in order to strengthen literary-based da’wah in the era of globalization.